Die Gottesfrage in den Schriften Kants - Sala, Giovanni B. (Zeitschrift für katholische Theologie, 2001)
The Quest for God takes up a central place in Kant's Work. The present essay traces the development of Kant's thought on God in its changing phases. In the writings of 1755 we find quite a positive estimation of the possibility to know God through our reason. In the important metaphysical treatise of 1763 Kant already brings, in addition to his own "Only Possible Argument in support of a Demonstration of the Existence of God", a critique of all Theology based upon speculative principles of Reason. It is this very critique which later Kant took up again, substantially unchanged, in his Critique of Pure Reason and which gave him the reputation of a destroyer of all proofs of God. Since in the meanwhile he had dropped his own "Only Possible Argument", he was left with an access to God only through the practical reason. Special attention is given in the essay to the reiterated versions of the moral proof, in which Kant was confronted with the obstacles arising out of the formalism and autonomy of his ethics. Since Kant holds firmly to the connection between morality and happiness the article discusses the question as to wether the moral proof necessarily involves a eudaemonistic moral.